Phosphate: a novel cardiovascular risk factor - Ketteler, Markus; Wolf, Myles; Ritz, Eberhard (European heart journal, 2013)
It has recently been recognized that even in the normal population high normal phosphate concentrations are associated with increased all-cause and cardiovascul